Gender disparities in physical, psychological, and cognitive multimorbidity among elderly hypertensive populations in rural regions - Yudong Miao; Jiajia Zhang; Jian Wu; Dongfang Zhu; Junwen Bai; Jingbao Zhang; Ruizhe Ren; Dan Guo; Mingyue Zhen; Jinxin Cui; Xinran Li; Wenyong Dong; et al. (International Journal for Equity in Health, 2024)
Abstract Background The prevalence of gender disparities in physical, mental, and cognitive disorders among elderly hypertensive individuals in rural areas remains unclear. This study evaluates these disparities and the factors contributing to multimorbidity in this demographic. Methods A face-to-face survey was conducted from July 1 to August 31, 2023, involving the hypertensive population registered with the National Basic Public Health Service Program in Jia County. Physical disorder was defined as having one or more self-reported chronic conditions other than hypertension. Participants experiencing anxiety or depression were as having a psychological disorder. The 9-item Patient Health Questionnaire (PHQ-9) was used to assess depression symptomatology, and anxiety symptoms were evaluated using the 7-item Generalized Anxiety Disorder questionnaire (GAD-7). Cognitive disorders were assessed using the Brief Mental Status Examination Scale (MMSE). Multifactorial logistic regression models were used to analyze factors affecting different disorder combinations in both genders. The net difference in multimorbidity prevalence between genders was determined using the propensity score matching (PSM). Results Out of 18,447 hypertensive individuals aged 65 years and above (42.28% men), the prevalence of multimorbidity was 30.64% in men and 38.67% in women. Outcomes included seven categories: physical disorders, psychological disorders, cognitive disorders, and four different combinations of these disorders. The primary outcome was the presence of two or more disorders. The prevalence of physical, psychological, and cognitive disorders and their four combinations were higher in women than in men; Key factors influencing multimorbidity risk included subjective health status, illness duration, medication history, blood pressure control, and lifestyle behaviors in both men and women. Post-PSM analysis revealed that women had a 6.74% higher multimorbidity prevalence than men. Conclusions Physical, psychological, and cognitive disorders, along with their various multimorbid combinations, significantly impact the elderly hypertensive population. Prioritizing a healthy lifestyle is essential to mitigate multimorbidity risks. Considering that the prevalence of multimorbidity is higher in women than in men with hypertension, sufficient sleep, maintaining a healthy waist circumference, and medication adherence are vital for managing blood pressure and reducing multimorbidity risks.